DESENVOLVIMENTO E PADRONIZAÇÃO DA ESCALA DE AVALIAÇÃO DA ANSIEDADE TRAÇO-ESTADO (EATE) - SILVA, FÁBIO CAMILO DA (2020)
Mental disorders such as depression and anxiety have shown exponential growth worldwide in recent years, with Brazil not being an exception. Parallel to this, there is currently no psychological test approved for the assessment of anxiety by the Psychological Test Assessment System (SATEPSI), causing the psychologist, in particular, the lack of complementary resources to assist in the diagnosis. Such factors motivated the accomplishment of this study, whose objective was to standardize a Trait-State Anxiety Assessment Scale, initially called EATE. The concepts of anxiety were defined from a review by the PRISMA method, followed by the analysis of books and other sources of information. The initial version of the EATE consisted of 40 items and studies of agreement between judges (KAPPA = 0,915), validity and accuracy were performed. The initial results indicated that the best factor solution would be the assessment of anxiety using four distinct factors, called anxious thoughts, symptoms, social discomfort and cognitive aspects. The analyzes also indicated that 8 of the 40 items initially foreseen did not correspond to the theoretical model and, therefore, the most appropriate was the exclusion of these, generating a final version of the EATE with 32 items. Other psychometric analyzes were performed considering this solution. The reliability indices were satisfactory both for the state anxiety assessment scale ( = 0,948), for the trait ( = 0,958) and also for each of its factors ( = 0,777 to  = 0,949). In addition, a parallel analysis and a confirmatory analysis indicated the adequacy of the 4 factor model. Validity studies with the Beck Anxiety Inventory (BAI) (r = 0,375 to r = 0,856, p <0.01) and the Brief Symptom Inventory (BSI) (r = 0,342 to r = 0,729) indicated the correlation between the constructs evaluated by both. Other studies, related to the variable academic experience, gender, type of university and age group also indicated satisfactory results for EATE. The analysis of the scores allowed to assign an initial cut-off point for the interpretation of the results consistent with the incidence of anxiety disorders in the Brazilian population. It is concluded that the pilot study generated the need for few changes to the final version of the EATE and that the results favor the continuity of the research with other groups that allow more precise analyzes and reach the parameters adopted by the Federal Council of Psychology ( CFP) for passing a psychological test. Among these, it is verified, mainly, the accomplishment of researches with clinical and control groups, so that EATE can be used as subsidy for differentiation between normal and pathological anxiety.